Isolation of rabbit single domain antibodies to B7-H3 via protein immunization and phage display. (17th February 2020) - Feng, Ruonan; Wang, Ruixue; Hong, Jessica; Dower, Christopher M; Croix, Brad St; Ho, Mitchell
Abstract: Single domain antibodies have certain advantages including their small size, high stability and excellent tissue penetration, making them attractive drug candidates. Rabbit antibodies can recognize diverse epitopes, including those that are poorly immunogenic in mice and humans. In the present study, we established a method to isolate rabbit VH single domain antibodies for potential cancer therapy. We immunized rabbits with recombinant human B7-H3 (CD276) protein, made a phage-displayed rabbit VH single domain library with a diversity of 7 × 10 9, and isolated two binders (A1 and B1; also called RFA1 and RFB1) from phage panning. Both rabbit VH single domains exhibited antigen-dependent binding to B7-H3-positive tumor cell lines but not B7-H3 knockout tumor cell lines. Our study shows that protein immunization followed by phage display screening can be used to isolate rabbit single domain antibodies. The two single domain antibodies reported here may have potential applications in cancer immunotherapy.